Legal Framework for Marine Oil Pollution Control in Tanzania - Gurumo, Tumaini Shabani (Advances in Social Sciences Research Journal, 2017)
Tanzania is among the countries in the west of the Indian Ocean. The country is endowed with maritime resources and a considerable coastline of about 1500 Kilometers. The well being of people leaving along the coast depend on the use of resources of the ocean. The country is facing current and potential danger of marine oil pollution caused by ships calling its ports and terminals, ships using the West Indian Ocean route, land based activities, and the developments in offshore oil and gas activities in the country and within East Africa region. In order to achieve sustainable use of the oceans and its resource, this article provide a legal framework for marine oil pollution control in the context of prevention of oil pollution, response to marine pollution incident and compensation for oil pollution damage. Specifically, the article assesses national legislation in the light of international agreements. The article assists in the analysis of the established legal regime and institutional framework for purposes of improving the status of marine oil pollution control.